ChemInform Abstract: Desymmetrization of Acid Anhydride with Asymmetric Esterification Catalyzed by Chiral Phosphoric Acid. Issue 50 (November 2016) - Yamada, Ken‐ichi; Oonishi, Akinori; Kuroda, Yusuke; Harada, Shingo; Kiyama, Hiroki; Yamaoka, Yousuke; Takasu, Kiyosei
Abstract: Using 2, 2‐diphenylethanol or diphenylmethanol as the nucleophile various σ‐symmetric carboxylic acid anhydrides are transformed in high yields and with high enantioselectivity into the corresponding half‐esters.